Errors in writing made by Malaysian rural primary school pupils - Halipah Harun; Muhammad Kamarul Kabilan (Universitas Syiah Kuala, 2020)
This study is to identify errors made by rural primary school pupils in writing and to get information about the causes or sources of errors that lead to pupils' writing problems. The conceptual framework concerns four types of errors committed by rural primary school pupils in writing, namely tense, spelling, and vocabulary. The study is based on Corder's (1971) Error Analysis (EA) and Richards' (1974) Causes or Sources of Errors as its theoretical framework. It was conducted at two rural schools with 44 pupils of Primary 5, aged 11, as the research sample. A written task was taken as the study instrument in order to answer two research questions. This study has revealed that tense is the most frequent error committed by the pupils, followed by punctuation, vocabulary, and spelling. Moreover, the pupils' errors are caused by both interlingual and intralingual transfer. It is concerned with rural primary school settings in Kerian where the majority of the pupils use the Malay language as their medium of instruction. In addition, this study has its implication for English Language Education in Malaysia, in which it affects rural pupils' performance especially in Primary School Achievement Test also known as Ujian Pencapaian Sekolah Rendah (UPSR) in English Writing paper. Some adjustments in the education system and the total involvement from education departments are meant to better reduce the number of low performers, especially in English writing to enhance the level of English proficiency in rural schools.